The role of foreign exchange dealers in providing overnight liquidity - Chris S'Souza (Bank of Canada, 2008)
This paper illustrates that dealers in foreign exchange markets not only provide intraday liquidity, they are key participants in the provision of overnight liquidity. Dealing institutions receive compensation for holding undesired inventory balances in part from the information they receive in customer trades. These flows can be used to forecast future movements in the exchange rate. Findings suggest that Canadian dealers, as a group and individually, are more likely to provide interday liquidity to foreign rather than Canadian financial customers. Financial institutions operating in multiple price-correlated markets manage their risky positions across markets. An interdependent relationship is revealed between the supply of liquidity provided by non-financial firms and dealing institutions across time, and across markets.
Keywords: F31; G21; D82; 330; Exchange rates; Market structure and pricing; Financial markets; Devisenhandel; Wechselkurs; Informationsbeschaffung; Tagesgeldmarkt; Bankenliquidität; Kanada; USA